2011
DOI: 10.1111/j.1538-7836.2011.04388.x
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient treatment in patients with acute pulmonary embolism: the Hestia Study

Abstract: Summary. Background: Traditionally, patients with pulmonary embolism (PE) are initially treated in the hospital with low molecular weight heparin (LMWH). The results of a few small non-randomized studies suggest that, in selected patients with proven PE, outpatient treatment is potentially feasible and safe. Objective: To evaluate the efficacy and safety of outpatient treatment according to predefined criteria in patients with acute PE. Patients and Methods: A prospective cohort study of patients with objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
176
2
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(207 citation statements)
references
References 35 publications
(44 reference statements)
14
176
2
5
Order By: Relevance
“…The remaining 11 studies were included in our systematic review. Eight were prospective cohort studies [8,[11][12][13][31][32][33][34]] and 3 were randomized controlled trials (RCT's) [16,17,35]. Furthermore, 2 studies did not report outcomes at 3 months and could not be used in our pooled meta-analysis [12,13].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining 11 studies were included in our systematic review. Eight were prospective cohort studies [8,[11][12][13][31][32][33][34]] and 3 were randomized controlled trials (RCT's) [16,17,35]. Furthermore, 2 studies did not report outcomes at 3 months and could not be used in our pooled meta-analysis [12,13].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported that outpatient management or early discharge of patients with acute PE is safe and effective [8][9][10][11][12][13]. Two systematic reviews suggested that patients with acute PE treated as outpatients had low incidences of major bleeding, recurrent venous thromboembolism (VTE), and mortality [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently published the results of a large prospective study in which clinical signs and symptoms were used to select patients with PE for outpatient treatment [6]. The Hestia criteria consist of 11 clinical criteria that can be used as a bedside test.…”
mentioning
confidence: 99%
“…While DVT has been treated as an outpatient for many years, recently developed risk stratification tools have been validated to select patients with PE who have a low risk of shortterm complications. [1][2][3][4][5][6][7] In particular, the Hestia criteria identifies a subgroup of PE patients who have a 1.0% mortality rate as outpatients over 3 months and a low rate of short-term complications requiring rehospitalization. 8 In this article, we assumed that many patients with DVT have undiagnosed PE and therefore must undergo the same risk stratification as patients with documented PE.…”
mentioning
confidence: 99%